Haiti and the United States - Dash, J. Michael. author. aut Link
XVII, 182 p.
Keywords: Imaginative literature, argues Michael Dash, does not merely reflect, but actively influences historical events. He demonstrates this by a close examination of the relations between Haiti and the United States through the imaginative literature of both countries. The West's mythification of Haiti is a strategy used to justify either ostracism or domination, a process traced here from the nineteenth-century until it emerges with a voyeuristic fierceness in the 1960s. In an effort to resist these stereotypes, Haitian literature becomes a subversive manoeuvre permitting Haitians to 'rewrite' themselves. The Unites States 'invented' Haiti as a land of savagery and mystery, a source of evil and shame. Weaving together text and historical context, Dash discusses the durability of these images, which continue to shape official policy and popular attitudes today.